(untitled) (Journal of Management and Social Sciences, 2025)
Nigeria’s rapidly expanding population has led to a substantial increase in its youth demographic, with individuals aged 15–35 accounting for over 30% of the total populace. This significant proportion positions youths as key actors in the country’s political, social, and economic spheres. Ideally, such a youthful population should translate into a productive and innovative workforce capable of driving sustainable development. However, Nigeria remains plagued by persistent poverty, a disengaged labor force, and socioeconomic stagnation. The growing discontent and agitation among Nigerian youths reflect these systemic issues. In light of these challenges, this study explores the intersection of political governance and ethnic and religious identity, with particular focus on how these factors influence youth political participation. It investigates the socio-political dynamics shaping youth engagement in Nigeria, chronicles historical patterns of youth involvement in governance, identifies obstacles impeding their active participation, and proposes actionable strategies to address these gaps. The study adopts a historical research methodology, utilising oral interviews and the analysis of relevant literature and archival materials. Findings reveal that the marginalisation of youths in Nigeria’s sociopolitical processes has significantly hindered national progress. Based on these insights, the paper advocates for the establishment of youth-centered policies and the deliberate integration of young people into the nation’s political framework as a pathway to sustainable national development. Keywords: Youth participation, political governance, ethnic identity, religious identity, national development, Nigeria